Travels in Southern Europe and the Levant, 1810–1817 : The Journal of C. R. Cockerell, R.A. - Cockerell, C. R. (Charles Robert), 1788-1863 (Cambridge library collection. Art and architecture., 1903)
The architect Charles Robert Cockerell (1788–1863) was encouraged to travel at a young age, so that he might draw inspiration from the great works of European architecture. However, when the Napoleonic Wars made parts of the continent inaccessible to Englishmen, his eye was turned towards southern Europe and the Ottoman Empire. This version of the Grand Tour took up seven years, during which he recorded the events in his journals. There his observations would have remained had it not been for the editorial labours of his son, Samuel Pepys Cockerell (1844–1921), who published the present work in 1903. The narrative takes in such cities as Constantinople, Athens, Florence and Rome. Touching also on friendships made with such figures as Byron, the text gives a sense of what continental travel was like at that time and how the architecture of the past continued to captivate designers in the modern age.